University Roles in Inservice Education Planning for Change - Carey, Lou M.; Marsh, David D.; American Association of Colleges for Teacher Education, Washington, DC. ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1980)
Intended to aid schools, colleges, and departments of education in the implementation of inservice teacher education programs or in the expansion of existing programs, this monograph presents current research findings on the role of the university in teacher inservice education. It outlines a step-by-step process for making such programs an integral part of the university's purpose and suggests that greater involvement can be effected by considering the problem as one of institutional change rather than merely as a question of faculty development. (Author/LH)
Sponsoring Agency: Office of Education (DHEW), Washington, DC. Teacher Corps.
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: College Role; Educational Research; Inservice Teacher Education; Institutional Cooperation; Program Development; Program Implementation; Research Utilization; Schools of Education; Teacher Education Programs; Information Analyses; Reports, Descriptive